2019
DOI: 10.1093/rheumatology/kez380
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids and steroid sparing medications monotherapies or in combination for IgG4-RD: a systematic review and network meta-analysis

Abstract: Objective To assess the safety and efficacy of glucocorticoids (GCs), immunosuppressive agents (IM) and rituximab (RTX), alone or in combination, for the treatment of IgG4-RD. Methods Relevant articles published were searched in the databases with relevant key words. Network meta-analysis was conducted, with various outcomes including relapse rate, remission rate and adverse events. Data were calculated with odds ratio (ORs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 37 publications
0
59
0
8
Order By: Relevance
“…These findings were further confirmed by a meta-analysis of 15 studies involving 1169 patients, whereby combination therapy with glucocorticoid and immunosuppressive drugs was associated with a lower relapse rate compared with glucocorticoids alone (odds ratio 0.39, 0.20 to 0.80) 120. Other scant reports, mostly focused on AIP, described positive experiences with tacrolimus, azathioprine, methotrexate, or leflunomide in preventing relapse of IgG4-RD, but these studies remain small, retrospective, and uncontrolled 120124125151…”
Section: Management Of Igg4 Related Diseasementioning
confidence: 68%
See 4 more Smart Citations
“…These findings were further confirmed by a meta-analysis of 15 studies involving 1169 patients, whereby combination therapy with glucocorticoid and immunosuppressive drugs was associated with a lower relapse rate compared with glucocorticoids alone (odds ratio 0.39, 0.20 to 0.80) 120. Other scant reports, mostly focused on AIP, described positive experiences with tacrolimus, azathioprine, methotrexate, or leflunomide in preventing relapse of IgG4-RD, but these studies remain small, retrospective, and uncontrolled 120124125151…”
Section: Management Of Igg4 Related Diseasementioning
confidence: 68%
“…Conversely, two prospective Chinese clinical trials showed a reduced relapse rate at one year when either mycophenolate mofetil (1-1.5 g/day) or oral cyclophosphamide (50-100 mg/day) was added to low dose corticosteroids, compared with steroid treatment alone (21% v 40% and 12% v 39%, respectively) 122123. These findings were further confirmed by a meta-analysis of 15 studies involving 1169 patients, whereby combination therapy with glucocorticoid and immunosuppressive drugs was associated with a lower relapse rate compared with glucocorticoids alone (odds ratio 0.39, 0.20 to 0.80) 120. Other scant reports, mostly focused on AIP, described positive experiences with tacrolimus, azathioprine, methotrexate, or leflunomide in preventing relapse of IgG4-RD, but these studies remain small, retrospective, and uncontrolled 120124125151…”
Section: Management Of Igg4 Related Diseasementioning
confidence: 80%
See 3 more Smart Citations